Imaginary bodies : ethics, power, and corporeality - Gatens, Moira (Routledge, 1996)
Moira Gatens investigates the ways in which differently sexed bodies can occupy the same social or political space. Representations of sexual difference have unacknowledged philosophical roots which cannot be dismissed as a superficial bias on the part of the philosopher, nor removed without destroying the coherence of the philosophical system concerned. The deep structural bias against women extends beyond metaphysics and its effects are felt in epistemology, moral, social and political theory. The idea of sexual difference is contextualised in Imaginary Bodies and traced through.